GERWANI IN THE COMMUNIST IDEOLOGY OF 1950-1965 - Rizqi Irza Afifi; Sofyan Kristianwantoni (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2019)
The emergence of Gerwani stems from the gathering of six women's organizations in Semarang on June 4, 1950 to merge their respective organizations into one single forum, namely Gerwis. Gerwis has a strong desire for the struggle for national independence and ending various political feudalism. In writing this article using the heirloom study approach. The results show that In December 1951 the name Gerwis changed to Gerwani. In 1964, Gerwani began designing work programs to develop himself and participate in politics. The programs include: Women's Rights; Children's Rights; Democratic Rights; Full National Independence; and peace.